DEVELOPMENT OF TRIGONOMETRY LEARNING PACKAGE BY APPLYING COGNITIVE STRATEGIES AND SCIENTIFIC APPROACH IN GRADE X AT SMA - Ernawati Madani (Universitas Negeri Makassar, 2015)
This study is research and development to produce learning package by applying cognitive strategy and scientific approach ini solving mathematics problem. The package include: (1) lesson plan, (2) student’s textbook, (3) teacher handbook, and (4) student’s worksheet. The development model used refers to 4-D model of Thiagaranjan, Semmel & Semmel which consists of defening phase, design phase, development phase, and dissemination phase. The study was conducted twice. The first tryout was conducted in grade X IPA 1 at SMAN 1 Bantaeng and the second tryout was conducted in grade X IPA 2 at SMAN 1 Bantaeng. The results obtained in the first tryout was: (1) the learning package is already practical, but still there are some suggestions need to be considered to improve the practicality of the package, (2) the learning package is yet effective because the classical completeness has not been achieved and students activity is not yet appropriate as expected, although the teacher’s ability to manage learning are already in high category and students’ response is already in positive category. The results of these analyzes are used to revise the package prior to the second trial. The results obtained in the second tryout were (1) the package is already practical, (2) the learning package is already effective, because the classical completeness has been reached, student’s activity is suitable as expected, the ability to manage the learning is in high category and students are already in positive category. Therefore, in the second tryout, prototype III was obtained which was valid, practical, and effective and continued with dissemination phase to obtain the final prototype. After 4 phases had been conducted, it is obtained learning package by applying cognitive strategies in solving mathematical problems which is are valid, practical, effective